Modele numerique de couplage fluide-structure avec application aux moteurs fusee - Lefran ois, Emmanuel; Dhatt, Gouri; Vandromme, Dany (European Journal of Computational Mechanics, 1999)
A finite element model is presented for studying fluid-structural interaction phenomena e. Domains are assumed axisymmetrical with flexible boundaries that may undergo large displacements. Newmark scheme is used for temporal discretization of structure part. Fluid is supposed compressible, inviscid and perfect. Numerical scheme for fluid is based on a LaxWendro. ff scheme taking into account moving mesh in order to respect parietal compatibilities. A schock capturing technique is added in order to maintain positivity scheme in high gradielll zones. After discussing considerations on a Geometrical Conservation Law, coupling is obtained in establishing a "dialogue" between both codes in using parallel tools to update common variables between fluid and structure. Two calculations are conducted on aeroelasticity with application to rocket engines.